Hydrocarbon Generation and Accumulation in the South Junggar Basin, Northwest China: Insights From Basin Modeling - Liu, Yuming; Lu, Xuesong; Zhao, Mengjun; Zhuo, Qingong; Gui, Lili (Frontiers in Earth Science, 2022)
The South Junggar foreland basin (SJFB) is characterized by fold-and-thrust deformation caused by the Cenozoic India–Tibet collision and uplift of the Tianshan Mountains. The tectonic deformation and hydrocarbon accumulation in this region show east-west, north-south, and vertical zoning. Four sets of source rocks are present in the basin, which are middle Permian, Middle–Early Jurassic, Early Cretaceous, and Paleogene in age. The various source rocks are vertically stacked and thus form a composite petroleum system. Due to differences in source rock distribution, hydrocarbon generation, and structural trap formation, the accumulation and distribution of oil and gas is spatially variable. In this study, we presented a detailed analysis of hydrocarbon generation and accumulation in the SJFB based on a combined basin modeling work both in 1D, 2D, and 3D single-well 1D modeling with measured temperature, and Ro data provide the suggested parameters, especially heat flow and erosion thickness, and then a simple 3D model was established based on the thickness maps of each formation and previous work on heat flow distribution. After 3D modeling, the results are rechecked with measured data and finally the source rock maturity map is obtained. By using the advanced “Block” function, the 2D modeling of complicated compressional structural sections has been successfully carried out. Four types of burial and thermal evolution history have been classified, which correspond to the different hydrocarbon phase and maturity. The heterogeneous distribution of oil and gas reflects the variable source rock distribution and maturity evolution, relative timing of hydrocarbon generation, and formation of structural traps. The timing of structural trap formation in the second and third row of anticlines was later than the main phase of hydrocarbon generation, which may explain the poor exploration outcomes in the SJFB. The result indicates that Jurassic and Cretaceous formations in the middle segment of the fold-and-thrust belt in the SJFB are the most favorable combination for hydrocarbon accumulations and have high potential for gas exploration.